The analysis of company's capital and evaluation of factors, which influence creation of the optimal capital structure - Saksonova, Svetlana (Journal of Business Economics and Management, 2006)
In this article, the author will outline several stages of the process of determining optimal capital structure and will concentrate in particular on the first two stages of this process – analysis of company's borrowed capital and equity as well as the evaluation of the main factors, which influence capital structure. It is important to stress these preparatory stages, because successful operation of the company is built on properly understanding the relationship between risk and potential reward that is inherent in different alternatives of capital structure. These stages stress the importance of gathering reliable financial information about the company (enabling calculation of the ratios mentioned in the article) and performing risk analysis (relying in part on the external and internal factors described in the article) in order to decide on the optimal capital structure. The author cautions that rapid economics growth in Latvia will at least slow down over time. Managers need to take that into account, when planning capital structure and therefore avoid increasing their leverage to dangerous levels.Firstd Published Online: 14 Oct 2010